Investigating the Synergistic Effect of Electrochemical Texturing and MoSeC Coatings on the Frictional Behaviour of Lubricated Contacts - Mahadeshwara, Manoj Rajankunte (2023)
The materials used for the piston cylinders of automobile engines, or the ring and tappets of various mechanical components, are continuously experiencing lubricated sliding motions. These surfaces are prone to damage due to the various tribological aspects of friction and wear. Hence, enhancing their surface properties would contribute to increasing their life and saving energy and resources. For many decades surface texturing and surface coating technology have been studied to improve the surface tribological behaviours of the materials. In the present study, the steel surface was textured with electrochemical processing (ECP) and post-coating with transition metal dichalcogenides (TMD) using a molybdenum-selenium-carbon (MoSeC) film. A comparative study was conducted to investigate the synergistic effect of surface texturing and coating to improve frictional properties on the steel surface. The block-on-ring experiments were performed under lubricated conditions to understand the improvement of COF at different lubrication regimes. It has been seen that the MoSeC-coated circular patterns exhibited improvements in the frictional properties at all the lubricated conditions if compared with smooth surfaces.